Translation, validation and extended factor models of the German State Difficulties in Emotion Regulation Scale (S-DERS) - Sicorello, Maurizio; Elsaeßer, Moritz; Kolar, David (Borderline Personality Disorder and Emotion Dysregulation, 2025)
Difficulties in emotion regulation are a key transdiagnostic factor in mental health disorders. While much research has focused on emotion regulation difficulties as stable, trait-like constructs, emotion regulation is inherently dynamic, unfolding over time. This highlights the need for state-like measures to capture these temporal dynamics in both laboratory and real-world contexts, such as the State Difficulties in Emotion Regulation Scale (S-DERS). The present study aimed to (a) translate the S-DERS into German, (b) validate its psychometric properties, and (c) provide novel examinations whether state-based emotion regulation difficulties share an underlying general factor or are interconnected but distinct sub-components, complemented with an exploratory network approach. A sample of 214 participants, predominantly young females, completed the 21-item German version of the S-DERS following a negative mood induction procedure. Participants also completed a broader battery of psychological assessments. Factor structure, reliability, and construct validity were examined using confirmatory factor analysis and exploratory structural equation modeling (ESEM) with cross-loadings. These were compared to bi-factor, higher-order, and network models. The German S-DERS demonstrated a robust four-factor structure, high reliability, and strong construct validity, consistent with the original English version. ESEM indicated that extensive cross-loadings were necessary to achieve good model fit. A four-factor correlated model outperformed both bifactor and higher-order models, suggesting that emotion regulation difficulties are best conceptualized as four distinct but interrelated constructs without a shared general factor: (a) Non-acceptance of Current Emotions, (b) Limited Ability to Modulate Current Emotional and Behavioral Responses, (c) Lack of Awareness of Current Emotions, and (d) Lack of Clarity about Current Emotions. The German version of the S-DERS is a reliable and valid tool for assessing state-like difficulties in emotion regulation. The extended factor models highlight the multidimensional nature of emotion regulation difficulties, with complex interrelations among distinct but related constructs. These insights can inform future research on emotion dysregulation and support efforts to validate the S-DERS in clinical populations.